Pendapatan dan Konsumsi terhadap Kesejahteraan Keluarga Petani Kopi - Darwin Damanik; Erlindo Ficky Nainggolan (Journal of Management and Bussines (JOMB), 2022)
This study aims to analyze the effect of household income and consumption on the welfare of coffee farming families in Salaon Tonga-Tonga Village, Ronggurnihuta District, Samosir Regency partially and simultaneously. The research method used is a quantitative and descriptive method of field research (survey). The type of data used in this study is primary data obtained from the results of a questionnaire of 100 coffee farmer respondents in Salaon Tonga-tonga Village, Ronggurnihuta District, Samosir Regency. The results showed that a) the income variable (X1) partially (individually) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; b) the consumption variable (X2) partially (individuals) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; c) the variable income (X1) and consumption (X2) simultaneously (together) have a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; d) the coefficient of determination (R Square) in this study is 0.427 (42.70%). This means that 42.70% of the independent variables (income and consumption) can explain variations in the dependent variable (welfare). While 57.30% is explained by other independent variables that are not included in this study. The conclusions in this study are, a) the income variable (X1) partially (individuals) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; b) the consumption variable (X2) partially (individuals) has a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency; c) the variable income (X1) and consumption (X2) simultaneously (together) have a significant effect on the welfare of coffee farming families in Salaon Tonga Tonga Village, Ronggurnihuta District, Samosir Regency. Keywords: Welfare, Consumption, Income, Coffee Farmers